Fenomena Representasi Simbolik Komunitas Mobil Toyota Fortuner Internasional Indonesia - Rina Sulastry (Syntax Corporation, 2023)
The study aims to examine more deeply the symbolic representation of the community of Toyota Fortuner International Indonesia car lovers Bengkulu Chapter. This research departs from the author's interest in researching this FOIIN community in depth, focusing on knowing the symbolic representation of the Toyota Fortuner International Indonesia car community and the motivations and goals of members to be interested in joining FOIIN members, while many other communities can be followed, whether only limited to having a Fortuner or because of other goals with the subject studied being a member of the FOIIN chapter community Bengkulu. In addition, the author also wants to know the views and perceptions of the public regarding the existence of the FOIIN car community in the Bengkulu chapter with the subject, namely people who know the existence of the FOIIN car community in the Bengkulu chapter. This research uses qualitative methods with a phenomenological approach and is analyzed using the Theory of Symbolic Interactionism proposed by George Harbert Mead using three basic assumptions, namely mind, self and society. Determination of informants in this study using purposive sampling techniques. Data collection techniques are carried out by observation, interviews, literature studies and documentation. The results obtained from this study show that it can be identified in the FOIIN Chapter Bengkulu community where some of these behaviors do not involve a thought process because they are only limited to responses to external challenges. Then an outward action was born where the community considered that the FOIIN Chapter Bengkulu community was a community with a luxurious member lifestyle.